THE EFFECT OF THE PREPARATION ‘AGRIMITIN’ ON WINTER WHEAT PRODUCTIVITY AND GRAIN QUALITY IN THE SOUTHERN PART OF THE ROSTOV REGION - A. A. Popov; G. V. Ovsyannikova; A. A. Sukharev; N. G. Dupliy (Зерновое хозяйство России, 2019)
The use of biological stimulants promotes plant metabolism, which improves the utilization of mineral fertilizers and plant defense mechanisms against the effect of unfavorable factors. The paper discusses the results of winter wheat seed treatment with ‘Agrimitin’ and a fungicide disinfectant ‘Vintsit Forte’. It has been determined that seed treatment with the preparations promoted the increase of winter wheat productivity. In 2017–2018 after seed treatment with ‘Agrimitin’, the average productivity increase was 0.18 t/ha for the winter soft wheat variety ‘Lydia’ and 0.25 t/ ha for the winter durum wheat variety ‘Lazurit’ compared with the productivity of the control variety. The combined use of preparations promoted the productivity increase on 0.37 t / ha for the winter soft wheat and on 0.44 t /ha for the winter durum wheat. The structural analysis of productivity showed that the use of preparations increased the number of productive stems to 580–648 pcs/ m2 in comparison with 564–621 pcs/m2 of the control variety. A number of kernels per ear and mass of kernels per ear of winter soft wheat after seed treatment had no significant increase. Winter durum wheat showed better effect of seed treatment: ‘number of kernels per ear’ increased from 30.6 pcs. to 32.8 pcs., and ‘mass of kernels per ear’ raised from 1.38 g to 1.55 g. The maximum profitability of winter soft and durum wheat production was identified in the variant with a combined use of the preparations ‘Agrimitin’ + ‘Protravitel’ (184.2% and 208.6% respectively). At the same time, the net income rate of winter soft wheat increased on 3,136 rubles/ha and that of winter durum wheat increased on 4,624 rubles/ha, compared to the the net income rate of the control variety (58145 rubles/ ha and 64796 rubles/ha, respectively).